Tantangan Komunikasi Pemasaran Terpadu Industri Perhotelan di Era Digital - Alif Sioux Ramli; Jokhanan Kristiyono (Jurnal Pewarta Indonesia, 2023)
The Covid-19 pandemic caused the hotel accommodation economy to stop, forcing 1,504 hotels across Indonesia to close. This situation forces hotel accommodation to innovate, by designing a recovery strategy until it arrives in the post-covid-19 pandemic. The right recovery strategy to develop is a marketing strategy, in order to increase motivation and be able to develop the company. Marketing Communication Mix is a marketing strategy that is often used by companies. In this study the researchers discussed "Marketing Mix Strategy in Post-Covid-19 Pandemic Hospitality Accommodation (Case Study: At Kokoon Hotel Surabaya)" with the aim of identifying and describing the 4P marketing communication mix strategy namely Product, Price, Promotion, and Place carried out by Hotel Kokoon Surabaya after the covid-19 pandemic. This research uses a case study method with a descriptive qualitative approach, in order to be able to describe the research results in a systematic, factual, and accurate manner. The results of this study stated that Hotel Kokoon Surabaya had utilized the 4P (Product, Price, Promotion, and Place) marketing communication mix strategy during the post-covid-19 pandemic. However, of the four elements, only one element uses all the attributes, namely the Promotion element. While the other three elements are only used as supporting elements.